Up‐regulation of DDIT4 predicts poor prognosis in acute myeloid leukaemia. Issue 1 (21st November 2019) - Cheng, Zhiheng; Dai, Yifeng; Pang, Yifan; Jiao, Yang; Liu, Yan; Cui, Longzhen; Quan, Liang; Qian, Tingting; Zeng, Tiansheng; Si, Chaozeng; Huang, Wenhui; Chen, Jinghong; et al.
Abstract: The mammalian target of rapamycin (mTOR) inhibitor, DNA damage inducible transcript 4 (DDIT4), has inducible expression in response to various cellular stresses. In multiple malignancies, studies have shown that DDIT4 participates in tumorigenesis and impacts patient survival. We aimed to study the prognostic value of DDIT4 in acute myeloid leukaemia (AML), which is currently unclear. Firstly, The Cancer Genome Atlas was screened for AML patients with complete clinical characteristics and DDIT4 expression data. A total of 155 patients were included and stratified according to the treatment modality and the median DDIT4 expression levels. High DDIT4 expressers had shorter overall survival (OS) and event‐free survival (EFS) than the low expressers among the chemotherapy‐only group (all P < .001); EFS and OS were similar in the high and low DDIT4 expressers of the allogeneic haematopoietic stem cell transplantation (allo‐HSCT) group. Furthermore, in the DDIT4 high group, patients treated with allo‐HSCT had longer EFS and OS than those who received chemotherapy alone (all P < .01). In the DDIT4 low group, OS and EFS were similar in different treatment groups. Secondly, we analysed two other cytogenetically normal AML (CN‐AML) cohorts derived from the Gene Expression Omnibus database, which confirmed that high DDIT4 expression was associated with poorer survival. Gene Ontology (GO) enrichment analysis showed that the genes related to DDIT4 expression were mainly concentrated in the acute and chronic myeloid leukaemia signalling pathways. Collectively, our study indicates that high DDIT4 expression may serve as a poor prognostic factor for AML, but its prognostic effects could be outweighed by allo‐HSCT.